Transport properties of hybrid topological superconductor devices in contact with an environment - Komnik, Andreas (Physical review, 2016)
We investigate the transport properties of different realizations of one-dimensional quantum wires coupled to a number of external electrodes in terms of the full counting statistics. Focusing on the setups in which edge states of Majorana type are realizable, we analyze the effects of the exchange of charge carriers with the environment. We find a very strong suppression of the nonlocal current correlations, which decay exponentially with the coupling strength and the wire length. Local properties such as transport currents and current correlations measured at individual contacts between the wire and external electrodes turn out to develop an asymmetry when they are energy resolved. We provide a number of exact analytical solutions and discuss experimental implications of our findings.
Gesehen am 14.05.2020